K.R. Eissler papers - Eissler, K. R. (Kurt Robert), 1908-1999.
Correspondence, writings, research files, and printed material documenting Eissler's research and writings on Sigmund Freud and his activities as secretary of the Sigmund Freud Archives. Includes research files from his book Freud und Wagner-Jauregg vor der Kommission zur Erhebung militärischer Pflichtverletzungen (1979) and a draft of Eissler's article (1981) critiquing Paul Roazen's book Brother Animal: The Story of Freud and Tausk (1969). Correspondents include Erik H. Erikson, Ernst Federn, Anna Freud, and Edoardo Weiss.
Mainly photocopies.
Psychoanalyst and author. Died 1999.
Collection material in English and German.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Sigmund Freud collection.
Keywords: Erikson, Erik H. -- 1902-1994 -- Correspondence; Federn, Ernst -- Correspondence; Freud, Anna, -- 1895-1982 -- Correspondence; Freud, Sigmund, -- 1856-1939.; Roazen, Paul, -- 1936-2005.; Tausk, Victor, -- 1879-1919.; Wagner-Jauregg, Julius von, -- 1857-; Weiss, Edoardo, -- 1889-1939 -- Correspondence; Sigmund Freud Archives; Psychoanalysis; Psychoanalysis -- Societies, etc; War neuroses; World War, 1914-1918.; Authors; Psychoanalysts